Single-phase cross-connected sources asymmetric T-type multilevel inverter with fault tolerant capabilities. (2nd February 2023) - Kumar, Vinay; Singh, Sanjeev; Jain, Shailendra
This work presents a cross-connected sources asymmetric T-type multilevel inverter (CCSATT-MLI) for single-phase operation with fault tolerant (FT) capabilities. The presented topology uses only one extra power semiconductor switch in the CCSATT 13-level (13L) inverter for fully FT operation. The paper uses two control schemes namely phase opposition disposition sinusoidal pulse width modulation (POD-SPWM) and nearest level control (NLC) for achieving the desired results under single switch open circuit (SSOC) fault. The obtained simulation results of proposed topology using MATLAB/Simulink are presented to show FT operation of the MLI under any SSOC fault. The simulation validations are validated under each switch fault using OpalRT hardware in loop (HIL) platform. The presented topology is also compared with recently reported MLI topologies for reduced number of count claim and effective FT operation in symmetric as well as asymmetric configurations.